1960
DOI: 10.1590/s0373-55241960000100002
|View full text |Cite
|
Sign up to set email alerts
|

A first appraisal of the landing and mechanism of the Santos fishery

Abstract: This paper summarizes and analyses the landing data collected at Santos, Brazil, during the 12 months period, July 1958-June 1959. These data are given in terms of weight landed of the more important fish and shrimp and also in terms of value. The distribution of the landings of each of the more important species is shown both according to the type of fishing gear used and fishing area. The fishing area is given in the form of statistical rectangles of 60 miles square. The landings are broken down to obtain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1962
1962
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…oeeanogn. da U~p. tration in the southern coast (Rio Grande do Sul State) (Richardson & Moraes, 1960;Lopez, 1963;Yamaguti & Moraes, 1965;Vazzo1er & Iwai, 1971), where it constitutes a distinct subpopu1ation from others at regions north of 28°s latitude (Yamaguti, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…oeeanogn. da U~p. tration in the southern coast (Rio Grande do Sul State) (Richardson & Moraes, 1960;Lopez, 1963;Yamaguti & Moraes, 1965;Vazzo1er & Iwai, 1971), where it constitutes a distinct subpopu1ation from others at regions north of 28°s latitude (Yamaguti, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…A pesca da corvina, efetuada pelos barcos de Santos, se faz ao longo da costa sul do Brasil, alcançando a costa do Uruguai, compreendendo desde o bloco de latitudes 23° sul e' 24° sul e longitudes 44° oeste e 45" oeste até o bloco de latitudes 34° sul e 35° sul e longitudes 54° oeste e 55° oeste, como mostra a Figura 1, restringindo-se a uma faixa de poucas milhas distante da costa (Braga, 1962;Richardson & Moraes, 1960).…”
Section: H -Pescaunclassified
“…In a paper (Richardson & Moraes, 1960) describing the landings of marine fish made at Santos, in the State of São Paulo, Brazil, it was shown that an appreciable weight of fish was landed as "Mistura". "Mistura" is a market category composed of a number of different species, including those sold by name as prime fish, but which, because of their small size, are not acceptable at the price paid for the named specieso Moreira (in preparation) gives a detailed analysis of the weight and numbers of each species included in "Mistura".…”
mentioning
confidence: 99%